Sozialrebell und Lumpensammler. Zur theoretischen Funktion von Marginalisierten bei Gramsci und Benjamin / Social Rebels and Rag Pickers. On the Theoretical Function of Marginalized Persons in Gramsci and Benjamin - Wagner, Birgit (International Gramsci Journal, 2023)
This contribution focuses on two marginalized figures, the social rebel Davide Lazzaretti in Gramsci and the rag picker in Benjamin. Whereas Gramsci’s social rebel is a historical figure, Benjamin’s rag picker is derived from Baudelaire’s famous poem “Le vin des chiffonniers” [“The Rag Picker’s Wine”]. These two case studies, if we may call them so (after all, they are both based on written texts only), discuss the importance of individual subaltern rebellions against the ruling capitalistic/patriarchal society of the nineteenth century. Both theoreticians emphasise what Adorno called “the claim of singularity to truth”, a claim inherent in their theoretical assumptions throughout their lifetimes. The analysis proves that Gramsci’s studies of the subaltern help to analyse even today’s issues; on the other hand, Benjamin’s remarks have a slight tendency to romanticize the figure of the “hero rag picker”, while being a testimony to the importance of literature for human memory and thereby an alternative way to understand the world. Thus, the two theoreticians highlight different approaches to today’s problems for us.